2011
DOI: 10.1209/0295-5075/96/66001
|View full text |Cite
|
Sign up to set email alerts
|

Stress tensor: A quantitative indicator of effective volume and stability of helium in metals

Abstract: We demonstrate a quantitative stress indicator as well as a qualitative hard-sphere lattice model to characterize the effective volume and stability of interstitial helium in fcc and bcc metals, based on extensive first-principles total-energy and lattice stress calculations in combination with continuum elastic theory analyses. The concept of stress indicator is believed to be generally applicable to quantify the relative stability of other inert gas elements in metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 32 publications
(49 reference statements)
2
5
0
Order By: Relevance
“…volume differences between the fully relaxed defect configurations and perfect lattice structures, are given in the last column of Table 1. The calculated relaxation volumes for vacancies and interstitial helium defects are in good agreement with literature data [14,15]. Table 1 show that the relaxation volume of nHe-v defects changes sign from negative to positive as the number of He atoms, occupying a vacancy, increases.…”
Section: Benchmarking Density Functional Theory (Dft) Calculationssupporting
confidence: 86%
See 1 more Smart Citation
“…volume differences between the fully relaxed defect configurations and perfect lattice structures, are given in the last column of Table 1. The calculated relaxation volumes for vacancies and interstitial helium defects are in good agreement with literature data [14,15]. Table 1 show that the relaxation volume of nHe-v defects changes sign from negative to positive as the number of He atoms, occupying a vacancy, increases.…”
Section: Benchmarking Density Functional Theory (Dft) Calculationssupporting
confidence: 86%
“…A recent study [16] of three inert-gases (He, Ne and Ar) defects in bcc-W modelled using a small 54-atom supercell gives the interstitial energy difference of 0.38 eV for the helium case (in comparison with 0.22 eV found here and in previous studies [9,10]), whilst for neon and argon, this energy difference is 0.62 eV and 1.06 eV compared to 0.51 eV and 1.13 eV found in our 128-atom super-cell study, respectively. Our nudged elastic band calculations give the migration barrier of 0.07, 0.14 and 0.23 eV for the tetrahedral interstitial He, Ne and Ar in a comparison with 0.06, 0.17 and 0.19 eV, respectively, found in [15]. The calculated formation energies of inert-gas atoms in substitutional positions shown in Fig.…”
Section: Benchmarking Density Functional Theory (Dft) Calculationssupporting
confidence: 54%
“…In the previous studies, [35,36] it has been demonstrated that a single He is energetically favorable sitting at the tetrahedral interstitial site (TIS) in the bulk V. However, the dissolution behavior of He in V GB is still unclear. Here, in order to find the most favourable site of a single He atom in the V GB, we examine the solution energies of all potential GB sites for He, including interstitial and substitutional cases.…”
Section: Dissolution Of Single He Atom In V Gbmentioning
confidence: 99%
“…Now, we discuss the possible physical origin underlying the behavior of the C/N-vacancy interaction in bcc vanadium. It is important to realize that, according to the normal understanding, a vacancy in most metals can open up more space (i.e., free volume) to bind any given solute such as hydrogen, [54][55][56] helium, [57][58][59] oxygen, [60][61][62] carbon, [63] and so on. Whereas in vanadium, the energy minimization finds the most stable position for the C/N solute to be at an Osite, which is off vacancy-center/vicinity (site 4 presented in Fig.…”
Section: The Property Of C/n-vacancy Interactionmentioning
confidence: 99%
“…In order to efficiently utilize the fusion power, tremendous efforts have been devoted to searching for the suitable structural materials in the last few decades. [7][8][9][10][11][12][13][14][15] In many experimental studies, vanadium and vanadiumbased alloys have been attested to be promising structural materials owing to their excellent performances at high temperatures, [16][17][18][19] such as the intrinsic low-activation characteristics, high-temperature strength, and high thermal stress factor, [17] all of which can satisfy the requirements of safety operation in the extreme conditions. However, some small atomic-radius elements such as carbon (C) and nitrogen (N) are always present in vanadium-based materials, either as alloying elements in vanadium or as impurities in pure vanadium solid.…”
Section: Introductionmentioning
confidence: 99%